Analysis of pseudoprogression after proton or photon therapy of 99 patients with low grade and anaplastic glioma. (February 2018) - Bronk, Julianna K.; Guha-Thakurta, Nandita; Allen, Pamela K.; Mahajan, Anita; Grosshans, David R.; McGovern, Susan L.
Highlights: No difference in pseudoprogression rate six months after proton or photon therapy. Oligodendrogliomas develop pseudoprogression sooner after protons vs. photons. Astrocytomas develop pseudoprogression at similar time after protons vs. photons. Abstract: Background and purpose: Proton therapy is increasingly used to treat primary brain tumors. There is concern for higher rates of pseudoprogression (PsP) after protons compared to photons. The purposes of this study are to compare the rate of PsP after proton vs. photon therapy for grade II and III gliomas and to identify factors associated with the development of PsP. Materials and methods: Ninety-nine patients age >18 years with grade II or III glioma treated with photons or protons were retrospectively reviewed. Demographic data, IDH and 1p19q status, and treatment factors were analyzed for association with PsP, progression free survival (PFS), and overall survival (OS). Results: Sixty-five patients were treated with photons and 34 with protons. Among those with oligodendroglioma, PsP developed in 6/42 photon-treated patients (14.3%) and 4/25 proton-treated patients (16%, p = 1.00). Among those with astrocytoma, PsP developed in 3/23 photon-treated patients (13%) and 1/9 proton-treated patients (11.1%, p = 1.00). There was no difference in PsP rate based on radiation type, radiation dose, tumor grade, 1p19q codeletion, or IDH status. PsP occurred earlier in oligodendroglioma patients treated with protons compared to photons, 48 days vs. 131 days, p < .01. On multivariate analyses, gross total resection (p = .03, HR = 0.48, 95%CI = 0.25–0.93) and PsP (p = .04, HR = 0.22, 95% CI = 0.05–0.91) were associated with better PFS; IDH mutation was associated with better OS (p < .01, HR = 0.22, 95%CI = 0.08–0.65). Conclusions: Patients with oligodendroglioma but not astrocytoma develop PsP earlier after protons compared to photons. PsP was associated with better PFS.